Kinetics of cadmium adsorption by CNTs grown on PACs - Mamun, Abdullah Al; AlSaadi, Mohammed AbdulHakim; Muyibi, Suleyman Aremu; Alam, Md Zahangir; Iis, Sopyan (Universiti Malaysia Perlis, 2014)
Isotherms and kinetic models are useful tool for the investigation of adsorption process. Carbon nanotubes (CNTs) grown on powdered activated carbons (PACs) was used as novel adsorbent. Two isotherms and three kinetic models were studied for the removal of cadmium from water. The isotherms were Langmuir and Freundlich and the kinetic models were pseudo first order, pseudo second order and intraparticle diffusion models. Langmuir constants were qm = 69.759 mg/g, Kl = 0.223 and R2 = 0.924. The adsorption process was found more likely to follow Freundlich model with R2 value of 0.961, Kf of 9.215 and n of 3.015. Based on the kinetics study, the pseudo second order was the best fit with R2 of 0.996 and model constants were qe = 34.29 (mg/g) and K2 = 0.0013 (g/mg.min). Coefficients for the pseudo first order were qe= 21.145 (mg/g) and K1= 0.09 (min-1) with R2 of 0.936. The intraparticle kinetic model exhibited R2 value of 0.812 with Kd = 1.295 (g/mg.min0.5). CNTs after oxidative functionalization with KMnO4 were observed to be an efficient adsorbent for Cd2+ removal from water.